SPECIFIC ASPECTS OF FOLK ART IN UZBEK AND TURKISH LANGUAGES - Babadjanova Umida Bakhodirovna (Journals Park Publishing, 2022)
This article talks about the unique aspects of the folk art in the Uzbek and Turkish languages. Genres of folklore, their composition, first of all, confirm that they are a whole heritage, apart from their division into gender, species, genres.
Keywords: Uzbek language, Turkish languages, folk art, speech art, literature.